Cause We Don’t Give a Dern: The Fundamental Tension Between Modern Copyright Law and American Folk Music - Asher Mitchell (Washington University Journal of Law and Policy, 2022)
Section 106(2) of the Copyright Act of 1976 provides the exclusive right to prepare derivative works based upon copyrighted work. This right is often invoked in the case of highly commercialized music to protect an artist’s interest in compensation for their work. While the derivative works right is essential in the music industry, it creates a divide between a copyright owner’s interest in compensation and the public’s interest in access. This Note delves into this divide and argues that the derivative works right is flawed in its attempt to cast a wide net over a host of creative mediums that are functionally different while paying little to no attention to how these mediums operate. Mitchell illustrates this dilemma through the lens of American folk music, a genre littered with musicians reinvigorating previous works. Mitchell argues that there exists an inherent tension between modern copyright law and American folk music traditions. To resolve this tension, Mitchell proposes a more discerning and intentionally under-inclusive ordinary observer standard and the establishment of a variety of license types so that copyright owners can opt out of strict protections. Mitchell argues that the combination of the two can solve the problems created by a rigidly applied statutory law and a musical tradition that relies heavily upon influences from others.
Keywords: Copyright Act of 1976; Derivative Works Right; American Folk Music; Copyright